Obesity: a silent killer / Ts Faikah Awang @ Ismail - Awang @ Ismail, Faikah (UiTM Cawangan Negeri Sembilan, 2022)
Eating is a natural need for humans. We eat to survive and be healthy and healthier bodies lead to advancing human achievement. But what if, the food that you eat become your silent enemy, slowly killing you every day? It sounds very alarming, yet we tend to ignore it as food is the source of our energy and for some people, it is a source of comfort. Eating food in a moderate amount and according to the guidelines suggested by a medical professional will help you in maintaining your health however if you take food without control for a long time it will lead you to develop the condition known as Obesity.